2021
DOI: 10.1080/02109395.2021.1950460
|View full text |Cite
|
Sign up to set email alerts
|

Sexting during confinement in Spain: prevalence, motivations and predictor variables (Sexting durante el confinamiento en España: prevalencia, motivaciones y variables predictoras)

Abstract: SARS-CoV-2 has resulted in the mandatory isolation of the entire population, reducing the opportunities for casual sexual encounters or between partners who do not live together. However, it is plausible to assume that other forms of sexual contact like sexting are occurring. This research aimed to analyse the behaviours and motivations to engage in sexting and to examine some predictors of mental health and loneliness that could be associated with sexting during confinement. The sample consisted of 510 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The prevalence reported by the participants of this study agrees with that found in previous research, where the wanted sexting behavior was more frequent than the unwanted (e.g., Ross et al, 2019). Furthermore, sending text messages with sexual con-tent was reported more commonly than sending pictures or videos, in accordance with similar studies (Gámez-Guadix et al, 2017;Garrido-Macías et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence reported by the participants of this study agrees with that found in previous research, where the wanted sexting behavior was more frequent than the unwanted (e.g., Ross et al, 2019). Furthermore, sending text messages with sexual con-tent was reported more commonly than sending pictures or videos, in accordance with similar studies (Gámez-Guadix et al, 2017;Garrido-Macías et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…We suggest that the scope of educational literature addressing unhealthy dating behaviors should be expanded to specify the difference between unwanted sexting and wanted sexting because nowadays, the latter is considered a new form of interpersonal communication that allows people to maintain sexual interactions, and it has been associated with positive consequences when done willingly (Döring, 2014;Drouin et al, 2017). Furthermore, data on the motives for sexting (Thomas, Binder, & Matthes, 2021), particularly the motives for unwanted sexting (Garrido-Macías et al, 2021), may be informative here and represent a next step in this line of research. A relationship has been found between motivations for sexting and aggressive online and offline behaviors (perpetration and victimization; Bianchi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%